2018
DOI: 10.15252/embj.201899845
|View full text |Cite
|
Sign up to set email alerts
|

Prominin‐1 controls stem cell activation by orchestrating ciliary dynamics

Abstract: Proper temporal and spatial activation of stem cells relies on highly coordinated cell signaling. The primary cilium is the sensory organelle that is responsible for transmitting extracellular signals into a cell. Primary cilium size, architecture, and assembly–disassembly dynamics are under rigid cell cycle‐dependent control. Using mouse incisor tooth epithelia as a model, we show that ciliary dynamics in stem cells require the proper functions of a cholesterol‐binding membrane glycoprotein, Prominin‐1 (Prom1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 71 publications
2
77
0
Order By: Relevance
“…The number of cells harboring no cilium was also increased upon expression of PROM1 Y819/828F mutants ( Fig. 1D) (33).…”
Section: Mutation Of Tyrosine 819/828 In Human Prom1 Reduces Ciliary mentioning
confidence: 84%
See 2 more Smart Citations
“…The number of cells harboring no cilium was also increased upon expression of PROM1 Y819/828F mutants ( Fig. 1D) (33).…”
Section: Mutation Of Tyrosine 819/828 In Human Prom1 Reduces Ciliary mentioning
confidence: 84%
“…The latter observation might be associated with the implication of prom1 in cancer cell migration (32). The selective binding of prom1 to ADPribosylation factor-like protein 13B (Arl13b) or histone deacetylase 6 (HDAC6) can orchestrate the functionality and dynamics of primary cilia, and consequently the activation of stem cells (33). The interactions of Prom1 with Arl13b/HDAC6 appear to be dependent on cytoplasmic lysine 138 (numbered according to prom1 splice variant s2) (33,34), while binding to Arp2/3 complex is stimulated by phosphorylation of a Cterminal tyrosine residue located at position 819/828 (s1/s2 variant) (28,35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Prominins have been shown to contribute to the generation and development of various cancers [4,6,86]. PROM1 is reported to be a regulator of stem cell activation by modifying microvillar architecture and dynamics and ciliary dynamics [12,18]. PROM2 can cause cellular protrusions and enhance phosphorylation of caveolin-1 to promote endocytosis [23].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PROM1 regulates metastasis, drug resistance, and stemness properties in various cancer cells [3,16,17]. It can also regulate the activation of stem cells by orchestrating ciliary dynamics, and the absence of PROM1 allows stem cells to resist the effects of sonic hedgehog (SHH) on growth stimulation, thereby disrupting stem cell activation [18]. Previous studies have shown that therapies targeting PROM1 may prevent tumor development in various human cancers [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%